Relationship Learning in Inter-Firm Conduits - Bhatti, Waheed Akbar (Vaasan yliopisto, 2018)
This dissertation investigates learning through relationship interactions, an essential component of knowledge development in the internationalization process of firms, employing the Uppsala model as a theoretical lens. The research question is, ‘How relationship learning influences the internationalization of firms and why is it critical?’ The dissertation comprises an integrative part, three published articles, and a conference paper. This research extends the understanding of how relationship learning through supplier-customer interactions can identify opportunities and exploit them for growth in the market. The qualitative thematic analysis of longitudinal data collected on supplier interactions from four multinational firms and four small and medium-sized enterprises in the manufacturing and service industries. It explores how learning takes place in a supplier-customer relationship and how acquired knowledge contributes to supplier processes for value creation through their offering. The dissertation contributes to the international business literature by studying micro-foundation level characteristics focusing on learning through knowledge sharing in inter-firm relationship interactions. This study helps to understand how the individual learning is an important means to, understand the customer needs and satisfy them. The case analyses demonstrate that relationship learning guides processes of knowledge development, and consequently the commitment decisions and their implementation. Socialization with customers paves the way for experiential learning that provides an insightful perspective for knowledge development. The study results highlight the importance of trust-building. It is evident that trust-building is an essential input in the commitment process. The results substantiate that the knowledge development processes and commitments take place at both ends of the relationship. This is a core element in understanding why the internationalization of organizations is an incremental process: both parties involved must engage and mutually work towards the process.

Väitöskirjassa tutkitaan oppimista yritysten välisissä vuorovaikutussuhteissa. Oppiminen on tärkeä tiedon kehittämiseen liittyvä komponentti yritysten kansainvälistymisprosesseissa. Teoreettisena lähtökohtana hyödynnetään ns. Uppsala-mallia. Tutkimuskysymyksenä on ”Kuinka suhteissa tapahtuva oppiminen vaikuttaa yritysten kansainvälistymiseen ja miksi se on kriittistä?” Väitöskirja koostuu yhdistelmäosiosta, kolmesta julkaistusta artikkelista ja yhdestä konferenssiartikkelista. Tutkimus lisää ymmärrystä, kuinka alihankkija-asiakas -vuorovaikutussuhteessa tapahtuva oppiminen voi auttaa tunnistamaan mahdollisuuksia sekä hyödyntämään niitä markkinoiden kasvattamiseksi. Tutkimuksen kvalitatiivinen teema-analyysi perustuu pitkittäisaineistoon, joka on kerätty alihankkijoiden välisestä vuorovaikutuksesta neljässä monikansallisessa yrityksessä ja neljässä pk-yrityksessä. Yritykset edustavat sekä valmistavaa teollisuutta että palvelutoimialoja. Väitöskirjassa paneudutaan siihen, kuinka oppimista tapahtuu alihankkija-asiakas -suhteissa, ja miten hankittu tieto vaikuttaa alihankkijan arvonluontiprosesseihin tarjooman kautta. Väitöskirja tukee kansainvälisen liiketoiminnan tutkimusta tuottamalla uutta tietoa erityisesti mikrotason ominaisuuksista keskittymällä oppimiseen yritysten välisissä suhteissa ja siinä tapahtuvaan tiedon jakamiseen. Tulokset auttavat oivaltamaan, kuinka yksilön oppiminen voidaan nähdä tärkeänä keinona ymmärtää asiakkaiden tarpeita ja tyydyttää ne sopivalla tavalla. Tapaustutkimukset osoittavat, että vuorovaikutussuhteessa tapahtuva oppiminen ohjaa tiedon kehitysprosessia sekä edelleen sitoutumiseen ja sen toteutumiseen liittyviä päätöksiä. Asiakkaiden kanssa tapahtuva sosialisaatio tasoittaa tietä kokemukselliseen oppimiseen, joka tarjoaa uusia näkökulmia tiedon kehittämiseen. Tulokset vahvistavat, että tiedon kehittämisprosesseja ja sitoutumista tapahtuu molempien osapuolten toimesta. Tämä on tärkeä tekijä ymmärrettäessä kuinka yritysten kansainvälistyminen etenee: molempien osapuolten pitää sitoutua ja työskennellä yhdessä prosessin tavoitteiden saavuttamiseksi.
Keywords: relationship learning; knowledge development; the Uppsala internationalization process model; oppiminen; yritykset; kansainväliset yritykset; kansainvälistyminen